1995
DOI: 10.1111/j.1365-2362.1995.tb01710.x
|View full text |Cite
|
Sign up to set email alerts
|

Decreased affinity of low density lipoprotein (LDL) particles for LDL receptors in patients with cholesteryl ester transfer protein deficiency

Abstract: We have reported that the disorder of lipoprotein metabolism in hyperalphalipoproteinaemic patients with a deficiency of cholesteryl ester transfer protein (CETP) is characterized by the polydisperse low density lipoprotein (LDL) particles and the accumulation of cholesteryl ester (CE) in high density lipoprotein (HDL) particles, forming cholesterol-induced HDL (HDLc)-like particles. In the present study we have investigated the interaction of these abnormal LDL with LDL receptors of normal human fibroblasts. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(29 citation statements)
references
References 53 publications
2
26
0
1
Order By: Relevance
“…The lipoprotein abnormalities in CETP deficiency are also characterized by the presence of polydisperse LDL enriched with triglycerides and large, CE-rich HDL particles. [11][12][13][14] These results indicated that CETP is involved in the regulation of plasma lipoproteins by modulating both the quantity and quality of each lipoprotein particle.…”
mentioning
confidence: 78%
“…The lipoprotein abnormalities in CETP deficiency are also characterized by the presence of polydisperse LDL enriched with triglycerides and large, CE-rich HDL particles. [11][12][13][14] These results indicated that CETP is involved in the regulation of plasma lipoproteins by modulating both the quantity and quality of each lipoprotein particle.…”
mentioning
confidence: 78%
“…This CETP effect could be related to its capacity to modify LDL's affinity for its specific receptors. Accordingly, Sakai et al (64) reported that CETP-deficient patients presented LDL particles with decreased affinity for LDL receptors. In another work (65), we showed that CETP transfers CE from OxLDL to HDL more efficiently than from native LDL.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Sakai et al have reported that the affinity of abnormal low-density lipoprotein (LDL) from CETP-deficient patients for the LDL receptor was largely decreased. 15 The delay in LDL catabolism is thought to result in increased opportunity for oxidation of LDL, and the change in LDL observed in patients with CETP deficiency could thus be atherogenic.…”
Section: Discussionmentioning
confidence: 99%